2009
DOI: 10.1053/j.gastro.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cells Mediate Leptin-Induced Liver Fibrosis

Abstract: Background & Aims-Leptin has pro-fibrogenic effects in liver, although the mechanisms of this process are unclear. We sought to elucidate the direct and indirect effects of leptin on hepatic stellate cells (HSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 50 publications
5
115
0
3
Order By: Relevance
“…Notably, a previous study confirmed that galanin inhibits leptin expression and secretion in rat adipose tissue and 3T3-L1 adipocytes (5). Leptin has been shown to possess direct profibrogenic activity in the liver, and the absence of leptin is associated with a marked attenuation of the hepatic response to a diverse range of fibrotic stimuli (6). It has been hypothesized that leptin acts directly on hepatic stellate cells (HSCs) to trigger downstream response pathways that ultimately lead to the deposition of extracellular matrix (ECM) (7).…”
Section: Introductionmentioning
confidence: 62%
“…Notably, a previous study confirmed that galanin inhibits leptin expression and secretion in rat adipose tissue and 3T3-L1 adipocytes (5). Leptin has been shown to possess direct profibrogenic activity in the liver, and the absence of leptin is associated with a marked attenuation of the hepatic response to a diverse range of fibrotic stimuli (6). It has been hypothesized that leptin acts directly on hepatic stellate cells (HSCs) to trigger downstream response pathways that ultimately lead to the deposition of extracellular matrix (ECM) (7).…”
Section: Introductionmentioning
confidence: 62%
“…In Kupffer cells, the transient activation of STAT3 by IL-6 is proinflammatory, promoting HSC survival and proliferation (10). The activation of STAT3 in HSCs by IL-6 or leptin stimulates HSC survival, proliferation, and activation (8,16,17). Nevertheless, the exact mechanisms of IL-6/STAT3 in HSC during liver fibrogenesis remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because of the emerging evidence indicating that angiogenesis is not only a critical component of chronic wound healing but can indeed favor liver fibrogenesis. Finally, it has also been reported that leptin, in addition to stimulate increased phagocytic activity and cytokine secretion by Kupffer cells and macrophages [58], may act indirectly on HSC by stimulating Kupffer cells to up-regulate their expression of TGFβ1 [59].…”
Section: Adipokinesmentioning
confidence: 99%